TEACHER'S PEDAGOGICAL COMPETENCE AS COMPLEX PERSONAL FORMATION (Pedagogy of Higher and Secondary Education, 2022)
This article considers the professional competence of a teacher as a complex personal unit, its structure and basic elements are analyzed.